Serum Free Zinc as A Predictor for Excessive Function of Pancreatic Beta-Cells in Central-Obese Men - Miftakh Nur Rahman; Indriyanti Rafi Sukmawati; Irma Melyani Puspitasari; Miswar Fattah (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: Central obesity is known as a risk factor for type 2 diabetes mellitus (T2DM). Its development is influenced by many factors such as a progressive failure of pancreatic beta cell function. The beta cells increase their function to secret insulin along T2DM development to compensate before it becomes exhausted. Zinc (Zn) plays a crucial role in beta cell function and insulin secretion. The majority of Zn in serum are bound to protein which is not readily available interact with cells. The free Zn in serum has been suggested as being more representative than total Zn in beta cell function. This research aimed to investigate the correlation between serum free Zn and homeostasis model assessment for beta cell function (HOMA-B) and to predict the pancreatic beta cell function in the development of T2DM.METHODS: This study was designed as an observational with a cross-sectional approach. The subjects were centrally obese men aged 30-50 years and who had met the inclusion and exclusion criteria from the screening tests. Control subjects were lean men without T2DM. Serum free Zn and serum total Zn were measured by using inductively coupled plasma-mass spectrometry (ICP-MS).RESULTS: There was positive correlation between serum free Zn and HOMA-B (R=0.361, p-value<0.001) but there was no correlation between serum total Zn and HOMA-B (R=-0.062, p-value=0.563). This study found that if the concentration of serum free Zn >1.7 ug/dL in central obese men was suggested as an excessive function of pancreatic beta cell and as an early warning before its exhausted.CONCLUSION: This study suggested that serum free Zn had a correlation with beta cell function and had a predictive ability for beta cell excessive function before its exhausted.KEYWORDS: Type 2 diabetes mellitus, HOMA-B, serum free zinc, central obesity